2008
DOI: 10.4161/cc.7.13.6095
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of centrosomal localization and dynamics of Cdc25C phosphatase in mitosis

Abstract: In mammalian cells, three Cdc25 phosphatases A, B, C coordinate cell cycle progression through activating dephosphorylation of Cyclin-dependent kinases. Whereas Cdc25B is believed to trigger entry into mitosis, Cdc25C is thought to act at a later stage of mitosis and in the nucleus. We report that a fraction of Cdc25C localises to centrosomes in a cell cycle-dependent fashion, as of late S phase and throughout G(2) and mitosis. Moreover, Cdc25C colocalises with Cyclin B1 at centrosomes in G(2) and in prophase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…Taken together, results in Figure 4 are consistent with the recognized association of Cdc2 with centrosomes, which are thought to be a platform for dephosphorylation of Cdc2 and activation of MPF, 56,[71][72][73] as well as with the spindle apparatus. 45,74,75 Cdc2 phosphorylates the tumor suppressor WARTS, a protein which associates with mitotic spindles and spindle poles, and regulates cell cycle progression via its interaction with zyxin, a regulator of actin filament assembly.…”
Section: Inactivation Of Cdc2 In Pde3asupporting
confidence: 84%
“…Taken together, results in Figure 4 are consistent with the recognized association of Cdc2 with centrosomes, which are thought to be a platform for dephosphorylation of Cdc2 and activation of MPF, 56,[71][72][73] as well as with the spindle apparatus. 45,74,75 Cdc2 phosphorylates the tumor suppressor WARTS, a protein which associates with mitotic spindles and spindle poles, and regulates cell cycle progression via its interaction with zyxin, a regulator of actin filament assembly.…”
Section: Inactivation Of Cdc2 In Pde3asupporting
confidence: 84%
“…1,2,34 Apart from their involvement in microtubule cytoskeleton and mitotic spindle organization, they are proposed to have a role as signaling platforms. 16,35,36 Particularly, it was proposed that centrosome or centrosome integrity is required for G 1 /S transition in cells with a preserved p53 but not in tumor cells with compromized p53-dependent cellular response. 17,19 Recently, additional studies have challenged this view and shown that the G 1 arrest is related to a stress response and not to a putative centrosome integrity checkpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies involve the centrosome in the progression between different cell cycle phases (reviewed in refs. [10][11][12][13][14][15][16]. However, there is a debate concerning the role of the centrosome in the control of the G 1 to S phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence study MDS-L cells were centrifuged onto cytospin slides and fixed for 30 s in 4% formalin/50% acetone, then permeabilized with lysis buffer including 0.2% Triton X-100, 25 mM HEPES, 60 mM PIPES, 10 mM EGTA and 2 mM MgCl 2 for 30 s. Antibody staining was performed using mouse monoclonal anti-aurora kinase A (BD biosciences, San Jose, CA, USA), rabbit polyclonal anti-CDC25C(Santa Cruz Biotechnology, Santa Cruz, CA, USA) to detect centrosomes, 23 and AlexaFluor488-or AlexaFluor594-conjugated anti-IgG antibodies (Molecular Probes, Eugene, OR, USA) as secondary antibodies. The nucleus was stained with DAPI (Dojindo, Kumamoto, Japan).…”
Section: Apoptosis Assaymentioning
confidence: 99%